Pendampingan Aplikasi Fungisida Heksakonazole: Upaya Penanganan Penyakit Patah Leher Tanaman Padi pada Kelompok Tani Tunggulrejo Bangkit di Desa Tunggulrejo Singgahan Tuban - Moh ihsan; M. Chairuddin (Journal of Innovation and Contribution to Community Service, 2025)
Rice blast disease, caused by Pyricularia oryzae, is one of the most destructive diseases in rice production, resulting in 15-20% yield losses in Indonesia. The Tunggulrejo Bangkit Farmer Group in Tuban Regency faced serious blast disease problems, with 80% of its members experiencing yield losses of 30-50%. This community service program aimed to provide mentoring for hexaconazole fungicide application to control blast disease and improve farmers' knowledge and income. The program was conducted from March to May 2025 using a Participatory Rural Appraisal (PRA) approach involving 25 farmers managing 32 hectares. The methodology consisted of five stages: initial survey, socialization and education, fungicide application training, demonstration plot establishment, and evaluation. The treatment plot received hexaconazole at 1.5 ml/L applied at 14, 35, and 55 days after planting, while the control plot used conventional practices. Results showed 78% control effectiveness, reducing blast disease intensity from 35-45% to 8-12%. Rice productivity increased 51% from 4.1 to 6.2 tons/ha. Farmers' knowledge scores improved from 55 to 85 points, with significant improvements in disease identification and fungicide application timing. Economic impact was highly favorable with additional net income of IDR 13,200,000 per hectare and benefit-cost ratio of 25.7. Technology adoption reached 85% in the subsequent season, demonstrating successful technology transfer and program sustainability